Dealing with difficult people (Harvard Business Review Press, 2018)
To resolve a conflict, first decide: is it hot or cold?: aim for warmth. Taking the stress out of stressful conversations: how to talk when you're emotionally entangled. The secret to dealing with difficult people: it's about you. How to deal with a mean colleague: stand up for yourself